Distance learning peculiarities at colleges in Ukraine - Zotyeva, Galyna; Vyrsta, Yaroslasv (НТУ "ХПІ", 2019)
The problem of distance learning implementation at colleges in Ukraine is considered. The relevance of the article is in the need of distance learning and use of the opportunities offered by that means of teaching. Distance learning main aspects, which create the necessary background for scientific achievements are systematized and analyzed in the article. Conceptual ideas of distance education in colleges and further perspectives for the development information and communication technologies in the distance education are investigated. The basis of the diagnosis and monitoring of the quality of education are curricula, programs, the content of which is set out by academic disciplines. The system of management of students in the conditions of distance learning implements the laws underlying the organization of the educational process.

Розглянуто проблему впровадження дистанційного навчання в коледжах в Україні. Актуальність статті полягає в необхідності дистанційного навчання та використанні можливостей, які надає цей спосіб навчання. У статті систематизовано та проаналізовано основні аспекти дистанційного навчання, які створюють необхідну основу для наукових досягнень. Досліджуються концептуальні ідеї дистанційної освіти в коледжах та подальші перспективи розвитку інформаційно-комунікаційних технологій у дистанційній освіті. Основою діагностики та моніторингу якості освіти є навчальні програми, програми, зміст яких визначається навчальними дисциплінами. Система управління студентами в умовах дистанційного навчання реалізує закони, що лежать в основі організації навчального процесу.
Особливості дистанційного навчання в коледжах в Україні
Keywords: distance education; on-line learning; information technologies; дистанційна освіта; он-лайн навчання; інформаційно-комунікаційні технології ІКТ